Effect of heat stress on physio-biochemical characteristics of chickpea (Cicer arietinum) genotypes - MEENA, NAND LAL; ALI, KISHWAR; DEHMUKH, P S; TYAGI, ARUNA (The Indian Journal of Agricultural Sciences, 2014)
A study was conducted with three chickpea genotypes Pusa 256, RSG 888 and JG 11 to study the effect of high temperature stress on various physiological and biochemical parameters. In all the chickpea genotypes high temperature stress decreased RWC, MSI, Chl content, dry matter, leaf area and increased activity of antioxidant enzymes such as POX, GR, and SOD. RSG 888 possessed better seedling growth parameters under high temperature as compared to Pusa 256 and JG 11.